If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8y + -2 = 14y + -3 Reorder the terms: -2 + 8y = 14y + -3 Reorder the terms: -2 + 8y = -3 + 14y Solving -2 + 8y = -3 + 14y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-14y' to each side of the equation. -2 + 8y + -14y = -3 + 14y + -14y Combine like terms: 8y + -14y = -6y -2 + -6y = -3 + 14y + -14y Combine like terms: 14y + -14y = 0 -2 + -6y = -3 + 0 -2 + -6y = -3 Add '2' to each side of the equation. -2 + 2 + -6y = -3 + 2 Combine like terms: -2 + 2 = 0 0 + -6y = -3 + 2 -6y = -3 + 2 Combine like terms: -3 + 2 = -1 -6y = -1 Divide each side by '-6'. y = 0.1666666667 Simplifying y = 0.1666666667
| 20-4(w+1)=9w-4(9+w) | | 3(s-5)-7(4s-7)= | | 2x+40=90 | | wx=-4 | | P=a+2 | | 9x-(-6x-6)=-24 | | -2-(6t+9)= | | y=6x+18 | | -510=-4+2x | | 11x+8=69 | | 2x+4x-8=34 | | 8y+10=16-8y | | 10x-7=3x+5 | | 15-5(3-8y)= | | -7(1+5x)+3=-8(4x+5) | | y=6sin(6x) | | 9(a-3)+2= | | 3.5x-20=2.4x-13 | | -x-x^2=14 | | 2x+4y=76 | | -7x+1=-12x-12 | | -5(1-5k)+5(-8k-2)=-4k-8k | | 12x-3=13x-1 | | 8y=2x | | 100-x=-81 | | 7+q-7q-6q+3= | | 6a-17=4a+1 | | -7(2n-6)=7(n+3) | | 8=z-7 | | 3+9z-8h= | | 7x-8=3(x+2) | | 15x-9x=48 |